A Fractional-Order Chaotic System with an Infinite Number of Equilibrium Points - Ping Zhou; Kun Huang; Chun-de Yang (Discrete Dynamics in Nature and Society)
A new 4D fractional-order chaotic system, which has an infinite number of equilibrium points, is introduced. There is no-chaotic behavior for its corresponded integer-order system. We obtain that the largest Lyapunov exponent of this 4D fractional-order chaotic system is 0.8939 and yield the chaotic attractor. A chaotic synchronization scheme is presented for this 4D fractional-order chaotic system. Numerical simulations is verified the effectiveness of the proposed scheme.